UNSUR RIBA DALAM FENOMENA PINJAMAN ONLINE (PINJOL) MENURUT M. SYAHRUR - Sobina Fatmawati; Qithrotun Nida Aulia (Al-Fath, 2022)
This article discusses usury in the phenomenon of online loans according to Muhammad Syahrur. Online loans (Pinjol) have become a popular trend among various groups, including housewives and students. This article employs an analytical-descriptive qualitative approach and gathers data through literature. The aim of this research is to enrich the knowledge, especially in the field of interpretation (tafsir). The results obtained from this research indicate that in the context of usury, Muhammad Syahrur establishes clear limits for lenders, specifying that the maximum permissible interest rate is 100% of the loan amount that can be imposed on borrowers, and it must not exceed this limit. M. Syahrur also categorizes situations where interest rates can be applied and where they are not allowed. In conclusion, there are three classifications of situations: usury occurs when loans are given to individuals who are weak and unable to repay the loan, but they are charged interest. Usury arises when loans are distributed to individuals who can only repay the principal installment, but they are charged interest. Usury emerges when loans are distributed to individuals who are not entitled to receive charity or groups that should receive interest-free loans, with an interest rate exceeding twice the amount of the principal installment.